Advances in wireless sensor networks : the 8th China Conference, CWSN 2014, Xi'an, China, October 31-November 2, 2014. Revised selected papers /: the 8th China Conference, CWSN 2014, Xi'an, China, October 31-November 2, 2014. Revised selected papers. (2015) - Unknown
No abstract available